Regulation of connexin 43 channels by PKC-mediated phosphorylation - Altenberg, G. A. (2008)
Gap-junctional channels communicate adjacent cells electrically and metabolically. They are formed by 4-transmembrane helix proteins called connexins; six connexins form a connexon (or gap-junctional hemichannel) and two of these, one from each neighboring cell, dock head-to-head to form the gap-junctional channel. The permeability of gapjunctional channels is regulated by voltage, intracellular calcium activity, intracellular pH and phosphorylation by various kinases. This review focuses on the mechanism of the regulation of connexin 43 by protein kinase C. We discuss results obtained largely from studies of hemichannels that demonstrate that the channel pore is narrowed down, but not closed, by protein kinase C-mediated phosphorylation of a single site, serine 368, located 14 residues away from the C-terminal end of connexin 43. The effect of protein kinase C involves a large conformational change of the protein and requires phosphorylation of all six subunits. The precise mechanism of the decrease in pore cross-sectional area has not been established.